Application of Alginate-chitosan edible coating incorporated with Cinnamon Leaf Oil (Cinnamomum Burmanii) on Cayenne Pepper (Capsicum Frutescens Linn.) Quality - Bara Yudhistira; Windi Atmaka; Aditya Pujasakti Yuswi (agriTECH, 2026)
Cayenne pepper (Capsicum frutescens L.) is a vegetable commodity widely consumed in Indonesia. However, the short shelf life indicates the need for treatment to inhibit metabolic processes. One method used to address this problem is the application of controlled atmospheric techniques through edible coating. Although numerous studies on edible coating have been conducted in Indonesia, further exploration is still needed to develop suitable formulations using biopolymers with desirable characteristics. Therefore, this study aimed to determine the effect of alginate-chitosan edible coating  (AK) and incorporation of cinnamon leaf oil (AKM) on the quality of cayenne pepper for 12 days of storage at room temperature (25-28°C). The results showed that based on analysis of variance (ANOVA) of 5% significance, the use of edible coating (AK) had a significant effect on color intensity, weight loss on day-3, as well as 2,2-diphenyl-1-picrylhydrazyl (DPPH) levels on day-0 and day-9. Meanwhile, the use of edible coating (AKM) had a significant effect on weight loss, color, hardness, DPPH levels on day-0 and day-6, vitamin C levels on day-9, and total microbes on day-12. The film formula with 3% alginate-3% chitosan had a significant effect (a: 0.05) on all chili quality parameters compared to other treatments. In conclusion, the application of alginate-chitosan edible coating incorporated with cinnamon leaf oil can maintain the physical, chemical, and microbiological qualities. This potential has significant applications in post-harvest handling of cayenne pepper on an industrial scale to maintain quality and increase economic value.